2016
DOI: 10.3390/ijerph13020155
|View full text |Cite
|
Sign up to set email alerts
|

Association between Psychological Flexibility and Health Beliefs in the Uptake of Influenza Vaccination among People with Chronic Respiratory Diseases in Hong Kong

Abstract: It is common for elderly people and those with such chronic disorders as respiratory diseases to suffer severe complications from influenza, a viral infection. The voluntary uptake of vaccination is vital to the effectiveness of influenza prevention efforts. The Health Belief Model (HBM) is the most commonly used framework in the field of vaccination behavior to explain the decision that people make to accept or refuse vaccination. In addition, psychological flexibility is considered helpful in causing people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 58 publications
2
34
1
Order By: Relevance
“…In line with this, the cognitive parameters of risk perception were frequently identified as significant barriers, i.e. perceiving the likelihood of getting the disease as low (HCP 4/117 [ 43 , 73 75 ]; Pregnant 1/35 [ 76 ]; Elderly 1/62 [ 77 ]; Public 9/191 [ 68 , 72 , 78 84 ]) and perceiving the severity of the disease as low (HCP 8/117 [ 44 , 85 91 ]; Pregnant 3/35 [ 92 94 ]; Chronic 3/45 [ 58 , 95 , 96 ]; Children 2/18 [ 97 , 98 ]; Elderly 4/62 [ 96 , 99 101 ]; Public 16/191 [ 65 , 71 , 72 , 81 , 83 , 99 , 102 111 ]). Additionally, perceiving oneself as less susceptible to the disease decreased the uptake of the influenza vaccine in 23 studies (HCP 4/117 [ 42 , 112 114 ]; Pregnant 3/35 [ 115 118 ]; Chronic 1/45 [ 95 ]; Children 1/18 [ 119 ]; Elderly 1/62 [ 99 ]; Public 11/191 [ 99 , 107 , 108 , 120 128 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, the cognitive parameters of risk perception were frequently identified as significant barriers, i.e. perceiving the likelihood of getting the disease as low (HCP 4/117 [ 43 , 73 75 ]; Pregnant 1/35 [ 76 ]; Elderly 1/62 [ 77 ]; Public 9/191 [ 68 , 72 , 78 84 ]) and perceiving the severity of the disease as low (HCP 8/117 [ 44 , 85 91 ]; Pregnant 3/35 [ 92 94 ]; Chronic 3/45 [ 58 , 95 , 96 ]; Children 2/18 [ 97 , 98 ]; Elderly 4/62 [ 96 , 99 101 ]; Public 16/191 [ 65 , 71 , 72 , 81 , 83 , 99 , 102 111 ]). Additionally, perceiving oneself as less susceptible to the disease decreased the uptake of the influenza vaccine in 23 studies (HCP 4/117 [ 42 , 112 114 ]; Pregnant 3/35 [ 115 118 ]; Chronic 1/45 [ 95 ]; Children 1/18 [ 119 ]; Elderly 1/62 [ 99 ]; Public 11/191 [ 99 , 107 , 108 , 120 128 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that unhealthy lifestyles have a negative impact on vaccine uptake, such as alcohol consumption (Chronic 1/45 [ 321 ]; Public 3/191 [ 345 347 ]) and smoking habits (Pregnant 3/35 [ 296 298 ]; Chronic 11/45 [ 95 , 249 , 321 , 325 , 348 354 ]; Elderly 9/62 [ 346 , 350 , 355 361 ]; Public 9/191 [ 317 , 346 , 347 , 361 366 ]). However, smoking was also a promoter in some cases (HCP 1/117 [ 367 ]; Public 3/191 [ 72 , 192 , 368 ]), and alcohol consumption did not reveal a clear picture in the reviewed studies (Pregnant 1/35 [ 297 ]; Elderly 1/62 [ 346 ]; Public 2/191 [ 346 , 365 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…How influential is a person’s trust in information from the health care system, personal doctors, pharmaceutical companies, government, or social media? How significant a factor is a person’s anxiety about vaccination infection [ 34 ] or fear of hypodermic needles [ 19 ]?…”
Section: Discussionmentioning
confidence: 99%
“…An influenza-induced fever is common and usually lasts two to four days [ 3 , 34 ]. Millions of people fall ill to influenza every year in the United States and recover in a few days [ 15 ].…”
Section: Discussionmentioning
confidence: 99%